Ius Commune (DIREITO COMUM) - Massaú, Guilherme Camargo (2009)
The text intends to delimit historically the expression of an important time in the formation of modern law, not by its mentality itself, but by the beginning of the specific study of Law at the universities. Moreover, it is in this a great historical cycle that arise the schools and the jurists of fundamental importance to the legal ambit. The Ius Commune does not ignore the realities with their legal manifestations of each region. The formation of the Ius Commune has the reception of Roman law through the study of the Corpus Iuris Civilis.